The Progression of Alzheimer's Disease Can Be Assessed with a Short Version of the CERAD Neuropsychological Battery: The Kuopio ALSOVA Study - Ilona Hallikainen; Janne Martikainen; Pei-Jung Lin; Joshua T. Cohen; Raquel Lahoz; Tarja Välimäki; Kristiina Hongisto; Saku Väätäinen; Matti Vanhanen; Peter J. Neumann; Tuomo Hänninen; Anne Maria Koivisto (Dementia and Geriatric Cognitive Disorders Extra, 2014)
Background/Aims: Measuring and predicting Alzheimer's disease (AD) progression is important in order to adjust treatment and allocate care resources. We aimed to identify a combination of subtests from the Consortium to Establish a Registry for Alzheimer's Disease Neuropsychological Battery (CERAD-NB) that best correlated with AD progression in follow-up as well as to predict AD progression. Method: A total of 236 participants with very mild [Clinical Dementia Rating (CDR) = 0.5] or mild AD (CDR = 1.0) at baseline were followed up for 3 years. The CERAD-NB and Mini-Mental State Examination (MMSE) were used to assess cognition, and the CDR scale sum of boxes (CDR-sb) was employed to evaluate AD progression. Generalized estimating equations were used to develop models to predict and follow up disease progression. Results: Performance declined on all CERAD-NB subtests. The ability of the separate subtests to distinguish between groups (baseline CDR = 0.5 or 1.0) diminished during follow-up. The best combination of subtests that explained 62% of CDR-sb variance in follow-up included verbal fluency, constructional praxis, the clock drawing test, and the MMSE. Baseline values of the same combination predicted 37% of the CDR-sb change. Conclusion: A short version of the CERAD-NB subtests provides a promising and time-efficient alternative for measuring cognitive deterioration during AD follow-up. Although the initial signs of AD include memory difficulties, it may be useful to assess non-memory tasks in follow-up.